Técnica de demodulación en señales biológicas - Gomez Lopez, Maria de Los Angeles (2004)
A new and modern technology to demodulate biological signals is described and evaluated for analogical and discreet signals. Applied methodology begins modulating a previously generated carrier by an intracardiac volume signal obtained from mamals. The Amplitud Modulated (AM) signal resulting is treated with the coherent demodulation technique. Professional Mathcad 7.0 mathematical software is used as work tool for digital-analogical conversion system.